PERANCANGAN SISTEM INFORMASI PENGGAJIAN PEGAWAI DAN GURU BERBASIS WEB MENGGUNAKAN METODE AGILE: STUDI KASUS SMKS PEMBANGUNAN KARYA JAMBE (Kohesi: Jurnal Sains dan Teknologi, 2025)
The goal of this research is to design and develop a web-based employee and teacher payroll information system using the Agile method at SMKS Pembangunan Karya Jambe. The school's manual payroll process often causes problems such as late payments, calculation errors, and a lack of transparency. These issues lead to dissatisfied honorary teachers and an increased workload for administrative staff. Therefore, a system is needed to automate the payroll process, improve efficiency, and provide greater transparency. The Agile method was chosen as the system development approach because it provides flexible, iterative, and adaptive solutions to changing user needs. The system development stages include planning, requirements analysis, system design, development, testing, implementation, and maintenance. The system is designed to fulfill functional needs, such as managing teacher data, calculating salaries, and generating payroll reports, as well as non-functional needs, such as speed, security, and scalability. The research results are expected to provide SMKS Pembangunan Karya Jambe with practical solutions for managing the honorary teacher payroll process more efficiently and accurately. Additionally, this system is expected to increase transparency and teacher satisfaction while reducing the workload of administrative personnel.